DNA Barcoding of Snapper Fish (Lutjanus spp.) from Kaimana and Fakfak, West Papua - Destia Fitri Ariyani; Wahyu Endra Kusuma; Bayu Pranata; Emmanuel Manangkalangi; Jeni Jeni; Abdul Hamid A. Toha; Muhammad Dailami (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
Kaimana and Fakfak are two regions in West Papua which have high biodiversity. The total fish production in Kaimana and Fakfak are 10,039 tons.y-1 and 17,806 tons.y-1, respectively. The snapper fish (Lutjanus spp.) is one of the important economic commodities in Kaimana and Fakfak regions. There has been a decrease in the number of exports of snapper fish in 2018 to 2019 from 4,742 tons to 4,290 tons due to overfishing and environmental pollution. This study employed DNA barcoding technology to identify the species of snapper fish collected from Kaimana and Fakfak. The DNA isolation was conducted by using genomic DNA mini kit (tissue) and the amplification of COI gene with Go Taq green master mix. Agarose gel electrophoresis was used to visualize the PCR product.  A total of 16 sequences with length 654 base pairs of COI gene were identified as five species of Lutjanidae, which were Lutjanus decussatus, L. gibbus, L. quinquelineatus, L. malabaricus, and L. johnii. Homology analysis with BLAST NCBI and BOLD System showed that all samples have similarity of 99.08-100% and query cover of 93-100%. Relationship analysis using phylogenetic tree and genetic distances showed results of intraspecific close relatives (0.001-0.016) and interspecific distant relatives (>0.1000). The phylogenetic tree illustrated that all species of Lutjanidae are separated into monophyletic clades. DNA barcoding technology successfully identified the snapper fish collected from Kaimana and Fakfak.